Effect of ZrB2 Particles on Machining Parameters of AA7475 Alloy-Based Composites by Optimization Technique. (2nd February 2023) - Mahesha, C. R.; Suprabha, R.; Suresh Kumar, R.; Chowdary, Chirumamill Mallika; Upadhyay, Viyat Varun; Soumya, M.; Al-Ammar, Essam A.; Palaniappan, Sivasankar; Diriba, Abdi
Abstract : ZrB2 particle-reinforced AA7475 is a potential material for high-performance aeronautical engine blades because of its exceptional characteristics. The machinability of ZrB2 /AA7475 metal matrix composites (MMC) is still a challenge because of the influence of ZrB2 particles. The impact of ZrB2 particulates on the machined parameters of ZrB2 /aluminum matrix composites was explored experimentally in order to meet the needs of industry. Additionally, the best machining circumstances for this type of material matrix composites were studied in this research. A surface roughness ( R a ) and metal removal rate (MRR) multiobjective optimization model was built, and a set of ideal parameter combinations was produced, with the surface roughness of ZrB2 /AA7475 material matrix composites being lower than that of the nonreinforced alloys at the same cutting speed.